2017
DOI: 10.1111/cen.13390
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association between testosterone, sex hormone‐binding globulin and metabolic syndrome: The Healthy Twin Study

Abstract: Both testosterone and SHBG were inversely associated with MetS although the inverse associations with the sex hormones were not consistently found across individual metabolic components. Findings from cotwin analysis suggest a significant contribution of unshared unique environmental effect to the association between testosterone and SHBG and abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…The production of testosterone by Leydig cells is stimulated by LH, which is synthesized in the anterior pituitary gland [29]. Similar to previous studies, in the young, healthy, male subjects included in our analysis, testosterone and SHBG were significantly inversely correlated with fasting glucose, HbA1c, WHR, BMI, lipid parameters (total cholesterol, LDL-C, apolipoprotein B, triglycerides), as well as inflammatory biomarkers [25,2831]. In observational studies it has been shown that men with lower testosterone levels are at higher risk for cardiovascular disease, and that subject on treatment with testosterone replacement therapy have a decreased risk of adverse cardiovascular events [28,32,33].…”
Section: Discussionsupporting
confidence: 82%
“…The production of testosterone by Leydig cells is stimulated by LH, which is synthesized in the anterior pituitary gland [29]. Similar to previous studies, in the young, healthy, male subjects included in our analysis, testosterone and SHBG were significantly inversely correlated with fasting glucose, HbA1c, WHR, BMI, lipid parameters (total cholesterol, LDL-C, apolipoprotein B, triglycerides), as well as inflammatory biomarkers [25,2831]. In observational studies it has been shown that men with lower testosterone levels are at higher risk for cardiovascular disease, and that subject on treatment with testosterone replacement therapy have a decreased risk of adverse cardiovascular events [28,32,33].…”
Section: Discussionsupporting
confidence: 82%
“…It is reported that lower TT and free testosterone (FT) levels are associated with hypertension. [6] However, some investigators have reported that TT and FT are not correlated with hypertension. [7,8] It has also been reported that lower SHBG is associated with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Free testosterone (FT) accounts for about 1–3% of total testosterone (TT). It’s generally regarded that decreased FT level was related to the presence of metabolic syndrome (MetS) [10, 11] and previous literatures proposed the regular test of FT in screening for hypogonadism [12]. Currently there’s been a few studies about FT in patients with PCa and the link between FT value and the aggressiveness of PCa has been demonstrated [13–16].…”
Section: Introductionmentioning
confidence: 99%